PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. JA JAYA ABADI DI KOTA DEPOK - Sharikha Qamara Leksono; Anisa Nurdina (Kampus Akademik Publiser, 2026)
This study aims to analyze the impact of Organizational Culture and Job Satisfaction on Employee Performance. The research employs a quantitative approach using a causal associative method. Data were collected through the distribution of questionnaires to employees who served as research respondents, and subsequently analyzed using linear regression analysis, correlation analysis, t-tests, and F-tests to examine the effects of each variable both partially and simultaneously. The findings reveal that the Pearson correlation coefficient between Organizational Culture (X1) and Employee Performance (Y) is 0.848, with a significance level of 0.000 < 0.05. This result indicates the existence of a positive and significant relationship between organizational culture and employee performance. Furthermore, the Pearson correlation coefficient between Job Satisfaction (X2) and Employee Performance (Y) is 0.864, with a significance value of 0.000 < 0.05, demonstrating a positive and significant relationship between job satisfaction and employee performance. Job Satisfaction is also proven to have a positive and significant effect on Employee Performance, as indicated by the simultaneous correlation coefficient (R) of 0.892. This value falls within the range of 0.80–1.00, which signifies a very strong relationship. The calculated F-value is 71.670 with a significance level of 0.000. Since the significance value is less than 0.05, H₀ is rejected and H₁ is accepted. This result indicates that Organizational Culture and Job Satisfaction simultaneously have a significant effect on Employee Performance. The high F-value suggests that the regression model has a strong ability to explain variations in Employee Performance when both independent variables are considered together. Therefore, it can be concluded that improving employee performance requires strengthening a positive organizational culture and enhancing employees’ job satisfaction..